2020
DOI: 10.1111/cas.14729
|View full text |Cite
|
Sign up to set email alerts
|

P300‐dependent acetylation of histone H3 is required for epidermal growth factor receptor‐mediated high‐mobility group protein A2 transcription in hepatocellular carcinoma

Abstract: High‐mobility group protein A2 (HMGA2) is highly expressed in hepatocellular carcinoma (HCC) cells and contributes to tumor metastasis and poor patient survival. However, the molecular mechanism through which HMGA2 is transcriptionally regulated in HCC cells remains largely unclear. Here, we showed that the expression HMGA2 was upregulated in HCC, and that elevated HMGA2 could promote tumor metastasis. Incubation of HCC cells with epidermal growth factor (EGF) could promote the expression of HMGA2 mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In addition, histone acetyltransferase p300 and hMOF are involved in inducing HCC migration and vascular invasion by mediating the acetylation of some oncogenes and enhancing their transcriptions ( Niu et al, 2020 ; Pote et al, 2020 ; Liang et al, 2021 ). Epigenetic activation of the microRNAs by histone acetylation also contributes to EMT process and HCC metastasis ( Zhang et al, 2013 ; Wen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, histone acetyltransferase p300 and hMOF are involved in inducing HCC migration and vascular invasion by mediating the acetylation of some oncogenes and enhancing their transcriptions ( Niu et al, 2020 ; Pote et al, 2020 ; Liang et al, 2021 ). Epigenetic activation of the microRNAs by histone acetylation also contributes to EMT process and HCC metastasis ( Zhang et al, 2013 ; Wen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…HMGA2 , which is reputedly critical for embryonic stem cell development, is highly expressed in pluripotent embryonic stem cells during embryogenesis 28 . Liang et al 29 reported that knockdown of HMGA2 reduces the number of lung metastases in tumour‐bearing mice. In the present study, HMGA2 enhanced HCC malignant behaviour, including cell proliferation, anti‐apoptosis, migration/invasion in vitro and tumour growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al found that the activation of epidermal growth factor receptor (EGFR) can inactivate GSK3β and thereby stabilizes PD-L1 expression, accounting for breast cancer cell immunosuppression [ 61 ]. Since hyperactivation of EGFR is frequently observed in hepatocellular carcinoma, which is associated with aggressive tumors and poor survival rates [ 62 , 63 ]. Therefore, it raises the possibility that EGFR/GSK-3β/PD-L1 pathway may suppress T-cell activity in HCC.…”
Section: Discussionmentioning
confidence: 99%